POLITIK HUKUM PENGISIAN JABATAN APARATUR SIPIL NEGARA OLEH PRAJURIT TNI - Hasan Efendi; Mardi Candra; Hedwig A. Mau (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
his research aims to analyze the legal politics of appointing Indonesian National Armed Forces (TNI) personnel to State Civil Apparatus (ASN) positions and the resulting legal implications. The study is grounded in recent regulatory developments, namely Law Number 20 of 2023 concerning the State Civil Apparatus and Law Number 3 of 2025 amending Law Number 34 of 2004 concerning the TNI, which allow active military personnel to occupy civil positions but spark debates regarding their compatibility with principles of civilian supremacy, military professionalism, bureaucratic neutrality, and the merit-based system. This study employs a normative legal research method using statutory, case, analytical, and conceptual approaches. Analysis is conducted using Legal Politics Theory and Legal Harmonization Theory. The findings reveal that legal policy has shifted from a strictly restrictive model to an accommodative-restrictive model. Nevertheless, placement practices beyond legal provisions result in weakened neutrality, accountability, TNI professionalism, and ASN meritocracy, as well as legal disharmony. Consistent implementation of regulations and legal harmonization are necessary to maintain a balance between defense interests and civil bureaucratic professionalism.